The Ties That Double Bind: Social Roles and Women's Underrepresentation in Politics - TEELE, DAWN LANGAN; KALLA, JOSHUA; ROSENBLUTH, FRANCES (The American political science review, 2018)
This paper theorizes three forms of bias that might limit women's representation: outright hostility, double standards, and a double bind whereby desired traits present bigger burdens for women than men. We examine these forms of bias using conjoint experiments derived from several original surveys—a population survey of American voters and two rounds of surveys of American public officials. We find no evidence of outright discrimination or of double standards. All else equal, most groups of respondents prefer female candidates, and evaluate men and women with identical profiles similarly. But on closer inspection, all is not equal. Across the board, elites and voters prefer candidates with traditional household profiles such as being married and having children, resulting in a double bind for many women. So long as social expectations about women's familial commitments cut against the demands of a full-time political career, women are likely to remain underrepresented in politics.